Government Effectiveness: A Global Comparative Analysis Using World Bank Governance Indicators - Sharaf Addin, Eltayeib Hussein Mahmoud (Public Governance, Administration and Finances Law Review, 2025)
This study analyses the effectiveness of government, which is crucial for a stable society, and it examines whether government effectiveness (GE) varies significantly across global regions and income groups. Using the World Bank’s Worldwide Governance Indicators (WGI) data over 2023, the study compares differences in GE scores among seven geographic regions and three income groups based on the ANOVA approach and Tukey’s HSD post-hoc tests. Due to its comprehensive and up-to-date comparison, the study offers new insights into institutional performance. Results indicated that the quality of GE differs significantly by region and income level. High GE scores consistently belong to high-income countries, whereas low-income countries, particularly those in Sub-Saharan Africa and South Asia, tend to be less effective in this regard. Regional differences also exist, with Europe, Central Asia and North America being more effective than other regions. These results suggested the need for policy enhancement and institutional development in the countries of the underperforming regions. Improving governance there is crucial for promoting inclusive growth, enhancing service delivery and achieving certain Sustainable Development Goals.